Physiology of Hyperuricemia and Urate-Lowering Treatments - Benn, Caroline L.; Dua, Pinky; Gurrell, Rachel; Loudon, Peter; Pike, Andrew; Storer, R. Ian; Vangjeli, Ciara (Frontiers in Medicine, 2018)
Gout is the most common form of inflammatory arthritis and is a multifactorial disease typically characterised by hyperuricemia and monosodium urate crystal deposition predominantly in, but not limited to, the joints and the urinary tract. The prevalence of gout and hyperuricemia has increased in developed countries over the past two decades and research into the area has become progressively more active. We review the current field of knowledge with emphasis on active areas of hyperuricemia research including the underlying physiology, genetics and epidemiology, with a focus on studies which suggest association of hyperuricemia with common comorbidities including cardiovascular disease, renal insufficiency, metabolic syndrome and diabetes. Finally, we discuss current therapies and emerging drug discovery efforts aimed at delivering an optimised clinical treatment strategy.